The impact of cytokinin on jasmonate-salicylate antagonism in Arabidopsis immunity against infection with Pst DC3000 - Naseem, Muhammad (Landes Bioscience, 2013)
Cytokinin has long been shown to be an essential modulator of growth and development in plants. However, its implications in plant immunity have only recently been realized. The interaction between jasmonate and salicylate pathways is regarded as a central backbone of plant immune defense. However, the effect of cytokinin on the jasmonate and salicylate mediated balance in plant immunity is still not known. Here, we analyze the impact of cytokinin on the jasmonate-salicylate antagonism in Arabidopsis immunity regarding infection with hemibiotrophic pathogen Pseudomonas syringae pv tomato DC3000 (Pst DC3000). Systems biology analysis of a refined hormone immune pathway model provides insights into the impact of cytokinin on the balance between jasmonate and salicylic acid pathways in Arabidopsis. Targeted experiments validate model simulations monitoring bacterial growth in wild type plants as well as in jasmonate pathway mutants. An integrated analysis shows that CK promotes the SA pathway of plant immunity and does not promote JA-mediated Arabidopsis susceptibility against infection with Pst DC3000. Finally, we discuss these results in the context of an emerging model of auxin-cytokinin antagonism in plant immunity.